The Impact of Nurse Navigator-Led Preoperative Education on Hospital Outcomes Following Posterolateral Lumbar Fusion Surgery. (September 2021) - Turcotte, Justin; Menon, Nandakumar; Andersen, Kristina; Stone, Deborah; Patton, Chad
Abstract : Beyond the spine-specific pathology, patient factors such as associated medical and psychosocial conditions, understanding of the treatment process, and the degree of patient activation—defined as the ability of the individual to utilize the available information and actively engage in making their healthcare decisions—can influence outcomes after posterolateral lumbar fusion (PLF) surgery. A retrospective observational cohort study of 177 patients undergoing PLF at a single institution was conducted. Patient demographics, medical and psychosocial risk factors, and outcomes were compared between patients who attended a nurse navigator-led group preoperative education course and those who did not. Patients attending the course were younger, more likely to undergo one-level fusion, less likely to undergo 5- or more-level fusion, and had less comorbidity burden as measured by the hierarchical condition categories score. No differences in psychosocial risk factors were observed between groups. Course attendees had a significantly shorter length of stay (2.12 vs. 2.60 days, p = .042) and decreased average hospital cost (U.S. 10, 149 vs. U.S. 14, 792, p < .001) than those who did not attend; no differences in other outcomes were observed. After controlling for differences in risk factors, patients enrolled in a preoperative education course demonstrated a statistically significant reduction in hospital cost (β=−4, 143, p < .001). Preoperative education prior to PLF surgery may reduce hospital cost, possibly through increased patient activation. Given the relatively high prevalence of psychosocial risk factors in this and similar patient populations, optimizing patient activation and engagement is important to achieve high value care. Based on our findings, nurse navigator-led preoperative education appears to be valuable in this patient population and should be included in enhanced recovery protocols.